Forage legumes in African crop-livestock production systems - Nnadi, L.A.; Haque, I. (1988)
Examines ILCA's research on forage legumes in the past few years; discusses the potential role of forage legumes in increasing crop-livestock productivity in sub-Saharan Africa; and outlines priorities for future research.